2020
DOI: 10.1038/s41416-020-01070-6
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for concurrent chemoradiotherapy for patients with stage III non-small-cell lung cancer

Abstract: When treating patients with unresectable stage III non-small-cell lung cancer (NSCLC), those with a good performance status and disease measured within a radical treatment volume should be considered for definitive concurrent chemoradiotherapy (cCRT). This guidance is based on key scientific rationale from two large Phase 3 randomised studies and meta-analyses demonstrating the superiority of cCRT over sequential (sCRT). However, the efficacy of cCRT comes at the cost of increased acute toxicity versus sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…The female gender was associated with a significantly lower risk of death in both stage IIIA and IIIB. Several studies have shown the female gender as a good prognostic factor ( 40 , 41 ). However, in one of the studies, no significant difference was found between genders in terms of survival (3-year survival, 29% versus 24%).…”
Section: Discussionmentioning
confidence: 99%
“…The female gender was associated with a significantly lower risk of death in both stage IIIA and IIIB. Several studies have shown the female gender as a good prognostic factor ( 40 , 41 ). However, in one of the studies, no significant difference was found between genders in terms of survival (3-year survival, 29% versus 24%).…”
Section: Discussionmentioning
confidence: 99%
“…The most (approximate 75–80%) prominent type of lung cancer is non-small-cell lung cancer (NSCLC) [ 1 3 ]. For the patients suffering from inoperable NSCLC, concurrent chemoradiotherapy (CCRT) is regarded as the standard first-line treatment (FLT) [ 4 6 ]. When performing the CCRT, traditional external radiotherapy is commonly used [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the patients suffering from inoperable NSCLC, concurrent chemoradiotherapy (CCRT) is regarded as the standard first-line treatment (FLT) [ 4 6 ]. When performing the CCRT, traditional external radiotherapy is commonly used [ 4 6 ]. However, traditional external radiotherapy is typically associated with radiation- related complications, and the radiological dosing is limited by the distance between the tumor and the surrounding healthy tissue and vital organs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive staging work-up required to assess the feasibility for curative-intent treatment, and the need for consultation with a multidisciplinary team, further complicates the optimal, individualized management of stage III patients. In patients with unresectable disease who are fit (Eastern Cooperative Oncology Group Performance Status 0-1), have adequate lung function, and have a disease that can be encompassed within a radical radiation volume, chemoradiation therapy (CRT) using platinum-based chemotherapy is the standard of care [6]. Concurrent CRT (cCRT) is typically favoured for these patients, owing to multiple clinical studies showing its superiority to sequential CRT in stage III patients [7].…”
Section: Introductionmentioning
confidence: 99%